Call for Action: Invasive Fungal Infections Associated With Ibrutinib and Other Small Molecule Kinase Inhibitors Targeting Immune Signaling Pathways. (27th September 2017) - Chamilos, Georgios; Lionakis, Michail S; Kontoyiannis, Dimitrios P
Abstract : An increasing number of invasive fungal infections (IFIs) has been recently reported in patients with lymphoid malignancies treated with BTK inhibitors. The surge in development of small molecule kinase inhibitors requires increased awareness and novel preventive strategies for IFIs.. Abstract: Opportunistic infections caused by Pneumocystis jirovecii, Cryptococcus neoformans, and ubiquitous airborne filamentous fungi have been recently reported in patients with hematological cancers historically considered at low risk for invasive fungal infections (IFIs), after receipt of the Bruton tyrosine kinase inhibitor ibrutinib. The spectrum and severity of IFIs often observed in these patients implies the presence of a complex immunodeficiency that may not be solely attributed to mere inhibition of Bruton tyrosine kinase. In view of the surge in development of small molecule kinase inhibitors for treatment of malignant and autoimmune diseases, it is possible that there would be an emergence of IFIs associated with the effects of these molecules on the immune system. Preclinical assessment of the immunosuppressive effects of kinase inhibitors and human studies aimed at improving patient risk stratification for development of IFIs could lead to prevention, earlier diagnosis, and better outcomes in affected patients.